Thermoregulation of exercising men in the morning rise and evening fall phases of internal temperature. Issue 2 (June 1995) - Torii, M; Nakayama, H; Sasaki, T
Abstract : The purpose of this study was to compare the thermoregulatory responses during exercise in the morning rise (0900 h) and evening fall phases (2000 h) in circadian variation of body temperature. Five healthy volunteers performed bicycle exercises at 30% and 60% of maximal aerobic power (VO2max) at 26 degrees C with a relative humidity of 50%. Whole-body sweat rate (SR), rectal (Tre), mean skin (Tsk) and mean body (Tb) temperature, pulmonary ventilation (VE), oxygen uptake (VO2), and carbon dioxide output (VCO2) and heart rate (HR) were measured during the experimental period. SR during exercise at 30% VO2max was significantly higher at 2000 h than at 0900 h. However, the circadian variation of SR during exercise was not observed at 60% VO2max. At the two experimental times, there were also no significant differences in VO2, VCO2, VE and Tsk in both workloads. In HR, Tb and Tre circadian effects were demonstrated as well as in workload levels. As Tb was plotted against SR during exercise, positive correlations were observed. The data showed that there was a parallel shift in the SR to Tb relationship during exercise in the morning and evening. This rightward shift indicated that there was an increased Tb threshold for the onset of sweating in the evening. Resting Tb at 2000 h was significantly higher when compared with Tb at 0900 h. The present results suggest that the circadian influence on the thermoregulatory response to exercise may be evident only at low workloads.